Towards a Systematic Understanding of How to Institutionally Design Scientific Advisory Committees: A Conceptual Framework and Introduction to a Special Journal Issue. Issue 9 (27th September 2018) - Hoffman, Steven J.; Ottersen, Trygve; Tejpar, Ali; Baral, Prativa; Fafard, Patrick
Abstract: Scientifically‐derived insights are often held as requirements for defensible policy choices. Scientific advisory committees (SACs) figure prominently in this landscape, often with the promise of bringing scientific evidence to decision‐makers. Yet, there is sparse and scattered knowledge about what institutional features influence the operations and effectiveness of SACs, how these design choices influence subsequent decision‐making, and the lessons learned from their application. The consequences of these knowledge gaps are that SACs may not be functioning as effectively as possible. The articles in this special journal issue of Global Challenges bring together insights from experts across several disciplines, all of whom are committed to improving SACs' effectiveness worldwide. The aim of the special issue is to inform future SAC design in order to help maximize the application of high‐quality scientific research for the decisions of policymakers, practitioners, and the public alike. In addition to providing an overview of the special issue and a summary of each article within it, this introductory essay presents a definition of SACs and a conceptual framework for how different institutional features and contextual factors affect three proximal determinants of SACs' effectiveness, namely the quality of advice offered, the relevance of that advice, and its legitimacy . Abstract : This essay provides an overview of the special issue by defining scientific advisory committees (SACs) broadly, introducing a framework for understanding their effectiveness, and summarizing the individual papers included. The aim of the special issue to inform future SAC design and help maximize the application of high‐quality scientific research in decision‐making is also disclosed.